ASSIMILATION OF PRODUCTION OF THERMO-MECHANICALLY HARDENED REINFORCING BAR WITH EFFECTIVE AND ECONOMICAL CUT, EQUIVALENT DIAMETER 5,5—8,0 mm and 500 H/mm2 - V. A. Matochkin; V. V. Savinkov; A. V. Gontaij; V. I. Shcherbakov (Литьë и металлургия)
The carried out team-work of NIIZHB and RUP “BMZ” enabled to receive new technological decisions at production of bale reinforcing bar, realization of which will increase reliability of reinforced-concrete constructions of buildings and installations.